Nb-Ti composite ultra-fast cooling 700 MPa grade green clean surface automotive frame steel plate and its manufacturing method
Patent Information
- Application Number
- CN202610914620.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-23
AI Technical Summary
但该方法生产的钢板表面仍有5~8 μm的氧化铁皮残留,粗糙度较大,不利于后续涂装和冲压工序
[0038]1.综合性能优良:通过Nb-Ti复合微合金化与超快冷工艺的协同作用,在较低的碳当量(Ceq≤0.45%)条件下,获得抗拉强度Rm≥700 MPa、断后伸长率A≥18%的优良综合性能,满足了700~750 MPa级汽车大梁钢对高强度与良好塑性的双重要求。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal material processing technology, specifically relating to an Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate and its manufacturing method. Background Technology
[0002] In recent years, with the rapid development of the automotive industry and increasingly stringent energy conservation and emission reduction regulations, automotive lightweighting has become a core issue in the industry. For commercial vehicles, the chassis is a significant component of the overall vehicle weight, and the beam, as the core load-bearing component of the chassis, has enormous potential for lightweighting. Research shows that increasing the strength level of beam steel from 500 MPa to over 700 MPa can reduce the thickness of components by 30% to 40% while maintaining the same load-bearing capacity, thus achieving a significant weight reduction effect. Therefore, high-strength automotive beam steel of 700 MPa grade and above is increasingly widely used in key structural components such as load-bearing chassis and heavy-duty truck longitudinal beams.
[0003] However, the production of traditional 700 MPa grade automotive frame steel faces numerous technical bottlenecks. Firstly, in terms of composition design, to improve hardenability and ensure sufficient high-strength microstructure after hot rolling, precious metal elements such as Mo and Cr are often added. This not only significantly increases alloy costs but also raises the carbon equivalent of the steel sheet, deteriorating weldability. Secondly, in terms of microstructure control, conventional laminar flow cooling processes struggle to consistently achieve uniform bainitic or martensitic microstructures, easily leading to microstructure inhomogeneity in the strip width direction and resulting in performance fluctuations. Some companies employ offline quenching and tempering processes, which, while improving microstructure controllability, involve complex procedures, long production cycles, and high energy consumption. Furthermore, regarding the balance between strength and plasticity, 700 MPa grade steel sheets obtained through traditional processes are mostly characterized by granular bainite or tempered martensite, with elongation generally below 15%, making it difficult to meet the high plasticity requirements of automotive frame stamping. Finally, in terms of surface treatment, almost all traditional 700 MPa grade beam steel plates need to undergo hydrochloric acid pickling before leaving the factory to remove hot-rolled iron oxide scale. Pickling process has problems such as large acid mist pollution, high waste acid treatment cost, easy to cause excessive corrosion of substrate and hydrogen embrittlement risk.
[0004] Patent CN107649522A discloses a method for controlling the surface quality of hot-rolled steel coils. This method involves cooling the hot-rolled steel to 580-660°C at a cooling rate of 20-60°C / s before coiling to control the thickness and composition of the oxide layer on the steel plate surface. However, the steel plates produced by this method still have 5-8 μm of residual iron oxide scale on the surface, resulting in a relatively high roughness, which is detrimental to subsequent coating and stamping processes.
[0005] The published patent CN101906584A achieves pickling-free processing by adding Cr to form a dense Fe3O4 oxide layer on the surface of the steel plate, but the alloy is expensive and the roughness problem remains unsolved.
[0006] The published patent CN103320683A proposes a three-stage continuous hydrochloric acid pickling process, which results in serious acid mist pollution.
[0007] The acid-free solution proposed in patent CN105369134A has a strength of only 400 MPa, which cannot meet the requirements of automobile beams for load-bearing capacity and lightweighting.
[0008] In summary, how to obtain automotive beam steel sheets with high strength, high plasticity, and a green and clean surface in a single hot rolling process under the premise of low cost and environmental friendliness, through innovative synergistic design of composition and process, is a technical problem that urgently needs to be solved. Summary of the Invention
[0009] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a green and clean surface automotive beam steel sheet with Nb-Ti composite ultra-fast cooling technology and a tensile strength of 700 MPa. Based on the composition of C-Mn series steel, this invention adopts a low-Si, low-carbon equivalent, Nb-Ti composite micro-alloying composition system, combined with controlled rolling and ultra-fast cooling processes, and employs EPS green and clean surface treatment to obtain a green and clean surface automotive beam steel sheet with a tensile strength Rm ≥ 700 MPa and an elongation after fracture A ≥ 18%. The objectives of this invention include:
[0010] (1) Through the synergistic effect of innovative Nb-Ti composite microalloying design and ultra-fast cooling process, high-strength and high-toughness automotive beam steel plates with tensile strength Rm≥700 MPa and elongation after fracture A≥18% are obtained in one go on the hot rolling line; (2) Through ultra-fast cooling process, supercooled austenite is retained to the bainite transformation zone to obtain a multiphase structure with fine bainite laths as the main component and a small amount of ferrite and retained austenite, so as to achieve a good match between strength and plasticity; (3) The nano-scale precipitation of Nb and Ti in the bainite transformation window produces a significant precipitation strengthening effect to compensate for the strength loss caused by the low carbon equivalent design; (4) The EPS green clean surface treatment process completely replaces the traditional pickling to achieve green and clean production; (5) A high-quality surface with surface roughness Ra=3.0~4.5 μm is obtained to meet the requirements of subsequent coating and stamping.
[0011] The first technical solution of this invention is to provide an Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate. The specific technical solution is as follows: the chemical composition by mass percentage is: C: 0.08%~0.12%, Si≤0.15%, Mn: 1.80%~2.10%, Als: 0.030%~0.060%, Ti: 0.060%~0.090%, Nb: 0.020%~0.040%, N≤0.008%, P≤0.015%, S≤0.005%, with the balance being Fe and unavoidable impurities.
[0012] The reasons for using the above-mentioned components are as follows:
[0013] Carbon (C) is the core element ensuring strength, achieving dual strengthening through interstitial solid solution strengthening and the formation of carbides with Ti and Nb. When the C content is too low (<0.08%), insufficient carbide precipitation makes it difficult to stably achieve a strength of 700 MPa; when the C content is too high (>0.12%), weldability is significantly deteriorated, hardening tendency and cold cracking sensitivity are increased, and the carbon equivalent is increased, reducing the low-temperature toughness and user performance of the steel plate. Considering both strength targets and weldability, this invention limits the C content to 0.08%~0.12%.
[0014] Si plays a role in solid solution strengthening and deoxidation. However, excessively high Si content (>0.15%) will form low-melting-point Fe2SiO4 (ferroolitic) during hot rolling. This complex oxide is tightly bonded to the matrix and is difficult to completely remove through subsequent EPS physical descaling, which will seriously affect the surface quality of the steel plate. Therefore, this invention limits the Si content to ≤0.15%.
[0015] Mn: Mn is a key element for improving the hardenability of steel plates. It can significantly reduce the critical cooling rate for bainite transformation, expand the bainite formation region, and make bainite transformation easier to achieve under continuous cooling conditions in industrial production. Mn can also improve the strength of steel plates through solid solution strengthening and enhance their low-temperature toughness. To obtain a uniform bainitic structure under ultra-rapid cooling conditions, the Mn content needs to be increased to 1.80%~2.10%. This range provides sufficient hardenability while avoiding problems such as center segregation and banded structure in the billet caused by excessive Mn content. Higher Mn content also significantly reduces the Ar3 temperature, expanding the temperature window for rolling in the non-recrystallization zone.
[0016] Ti: Ti is an important precipitation strengthening element in this invention. It plays a triple role in steel: First, under high-temperature conditions (>1200 ℃), it combines with N to form stable TiN particles. These particles effectively pin austenite grain boundaries during heating and rolling, inhibiting grain growth and refining the original austenite grains. Second, during rolling in the non-recrystallization zone, the solid-solution Ti inhibits the recrystallization of deformed austenite through the solute dragging effect, synergistically refining the final microstructure with Nb. Third, during cooling and coiling, nano-sized TiC disperses and precipitates between and within bainite laths, producing a strong precipitation strengthening effect. Studies have shown that with increasing Ti content, the yield strength, tensile strength, and yield ratio of Ti-containing microalloyed low-carbon steel all increase to varying degrees. If the Ti content is too low (<0.060%), the precipitation strengthening and grain refinement strengthening effects will be insufficient; if it is too high (>0.090%), it is easy to form coarse high-temperature TiN or Ti(C,N) inclusions, which will impair the toughness and fatigue performance of the steel plate. Taking all factors into consideration, the present invention limits the Ti content to 0.060%~0.090%.
[0017] Nb: Nb is another core microalloying element in this invention. Compared with Ti, Nb is more effective in suppressing austenite recrystallization and is key to achieving an ultrafine grain structure in 700 MPa grade beam steel. Nitrogen (Nb) plays multiple roles in steel: First, during heating, a small amount of undissolved Nb(C,N) particles can pin austenite grain boundaries, inhibiting austenite grain growth and refining the original austenite grains. Second, during rolling in the non-recrystallization zone, strain-induced precipitation of Nb(C,N) strongly inhibits the recrystallization of deformed austenite, allowing a large amount of deformation energy (dislocations, deformation bands, and twins) to accumulate in the deformed austenite, providing numerous nucleation sites for subsequent phase transformations. Third, Nb dissolved in austenite further inhibits recrystallization and delays ferrite phase transformation through the solute dragging effect, enabling supercooled austenite to complete bainitic phase transformation at a lower temperature and refining the bainite lath size. Fourth, during cooling and coiling, nano-sized NbC precipitates in the ferrite and bainite matrix, producing a significant precipitation strengthening effect. Studies have shown that when Nb is added in combination with Ti, the amount of carbonitride precipitation increases non-linearly, and the strengthening efficiency is significantly higher than that of single addition. When the Nb content is below 0.020%, the effects of grain refinement strengthening and precipitation strengthening are not significant; when it is above 0.040%, coarse primary precipitates are easily formed, which impairs the toughness of the steel plate and increases costs. Therefore, this invention limits the Nb content to 0.020%~0.040%.
[0018] Nitrogen (N) is a key element in the formation of carbonitrides in Ti-Nb microalloyed steel. Appropriate amounts of N preferentially combine with Ti, precipitating fine, dispersed TiN particles during heating above 1200 °C and rough rolling, effectively pinning austenite grain boundaries and inhibiting grain growth. Simultaneously, N participates in the formation of (Nb,Ti)(C,N) composite precipitates at low temperatures, increasing the volume fraction of precipitates and improving precipitation strengthening. However, when the N content is too high (>0.008%), the high-temperature TiN particles will grow excessively and coarsen, reaching sizes of 5-10 μm. This not only loses its grain boundary pinning function but also becomes a stress concentration source and fatigue crack initiation point, severely impairing the steel's toughness and plasticity. Furthermore, excessive free N can combine with Nb to form large-sized Nb(C,N) precipitates, weakening Nb's role in inhibiting recrystallization during rolling. Therefore, this invention limits N to ≤0.008%.
[0019] Als: Al is a deoxidizing element in steel, which reduces oxide inclusions and purifies the steel, thus improving the formability of the steel sheet. Simultaneously, Al can form AlN precipitates, refining the grain size. Therefore, the optimal range of Als in this invention is 0.030%~0.060%.
[0020] S and P: Both S and P are harmful elements. P tends to segregate at grain boundaries, reducing grain boundary bonding and significantly deteriorating the low-temperature toughness and weldability of steel plates. S combines with Mn to form MnS inclusions, reducing the plasticity and toughness of steel plates and leading to anisotropy. The lower their content, the better. However, excessively low content increases production costs. Without affecting the performance of the steel plate, their content is limited to P ≤ 0.015% and S ≤ 0.005%.
[0021] Carbon equivalent Ceq: To ensure excellent weldability of the steel plate, the carbon equivalent must be controlled within the low weld crack sensitivity range recommended by the International Institute of Welding. Calculated using the formula Ceq=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15, the carbon equivalent Ceq of this invention is ≤0.45%.
[0022] Preferably, the microstructure of the steel plate comprises bainite, ferrite, and retained austenite, wherein the volume fraction of bainite is 80%~90%, the volume fraction of ferrite + retained austenite is 10%~20%, and the average grain size is grade 12 or finer. The fine bainitic lath microstructure provides high strength to the steel plate, while the small amount of ferrite and retained austenite provides plasticity.
[0023] Preferably, the steel plate has a yield strength ReL≥600 MPa, tensile strength Rm≥700 MPa, elongation after fracture A≥18%, surface roughness Ra=3.0~4.5 μm, surface cleanliness Sa not lower than level 3, and finished thickness of 1.5~10 mm.
[0024] The second technical solution of this invention provides a method for manufacturing Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate, including smelting, continuous casting of medium and thin slabs, heating, controlled rolling, ultra-fast cooling process, and EPS green and clean surface treatment process. The specific steps of this manufacturing method are as follows:
[0025] Medium-thin slab continuous casting: The medium-thin slab continuous casting process is adopted, and the thickness of the continuously cast slab is controlled at 135~200 mm. Compared with the traditional 225~250 mm thick slab continuous casting and rolling process, medium-thin slab continuous casting can effectively shorten the production line length and reduce energy consumption.
[0026] Heating process: The continuously cast billet is heated in a walking beam furnace at a temperature controlled between 1220 and 1260 °C, with a holding time of 1–3 h. Higher heating temperatures ensure that Ti and Nb carbonitrides are fully dissolved in austenite, preparing for subsequent nanoscale (Ti,Nb)C dispersion precipitation. Studies show that with increased heating temperature, microalloying elements dissolve more completely, resulting in more dispersed and abundant second-phase precipitates after rolling, which is a crucial basis for improving strength. Below 1200 °C, Ti dissolution is insufficient; above 1260 °C, austenite grains coarsen rapidly, and TiN particles begin to coarsen and lose their grain boundary pinning effect.
[0027] Controlled rolling and ultra-fast cooling processes: These are the core processes for obtaining ultra-fine bainitic microstructure.
[0028] Controlled rolling stage: A two-stage controlled rolling process is adopted, with a finishing rolling temperature of 980~1050 ℃ and a finishing rolling temperature of 800~850 ℃. The finishing rolling temperature of 800~850 ℃ is about 110~160 ℃ higher than Ar3, which ensures that the rolling process is completed in the single-phase austenite region, effectively avoiding the microstructure inhomogeneity and property fluctuations caused by rolling in the two-phase region. Rolling is carried out in the non-austenite recrystallization region (below 950 ℃), and through multi-pass large cumulative reduction deformation, a large amount of deformation energy (dislocations, deformation bands, and twins) is accumulated in the deformed austenite, providing a large number of nucleation sites for subsequent phase transformation and effectively refining the final microstructure. Nb can strongly inhibit austenite recrystallization in the temperature range of 800~950 ℃, which is the key to ensuring the cumulative deformation effect.
[0029] Ultra-rapid cooling stage: Immediately after final rolling, the steel plate undergoes ultra-rapid cooling at a rate ≥50 ℃ / s, rapidly cooling to the bainite transformation zone of 480~550 ℃ for coiling. The bainite phase transformation is completed during the slow cooling process after coiling. The main purposes of ultra-rapid cooling are: First, to allow supercooled austenite to pass through the high-temperature ferrite and pearlite transformation zone (approximately 700~750 ℃) at an extremely high cooling rate, bypassing the formation of these soft phase structures; Second, to retain most of the supercooled austenite within the bainite transformation window of 480~550 ℃, where it fully transforms into fine lath bainite during the slow cooling process after coiling; Third, within the bainite transformation window, the solubility of Ti and Nb elements dissolved in the matrix decreases sharply due to the decreasing temperature, precipitating out as nano-sized (Ti,Nb)C particles between and within the bainite laths, producing a strong precipitation strengthening effect.
[0030] EPS green cleaning surface treatment process: After the steel coil is uncoiled and straightened, it enters the EPS (Eco Pickled Surface) unit. Using water and steel grit as the medium, hot-rolled iron oxide scale is removed by physical jetting. The core component of the EPS unit is two sets of high-speed rotating turbines positioned vertically opposite each other. The turbine blades accelerate the mixture of steel grit and water to a linear velocity of 65~75 m / s, and simultaneously spray it onto the steel plate surface from both sides at a 60° incident angle, peeling off the iron oxide scale through abrasive impact.
[0031] Preferably, in the EPS process window, the turbine speed is 2000~2400 rpm, the steel plate travel speed is 20~30 m / min, the steel grit mesh is 50~60 mesh, and the corresponding average particle size is about 210~270 μm.
[0032] Furthermore, to ensure a surface roughness Ra ≤ 5.0 μm and a cleanliness Sa ≥ 3, the process parameters and steel plate properties must satisfy the following relationship:
[0033]
[0034] In the formula: n Turbine speed, rpm; v Let be the speed of the steel plate, in m·min -1 ; d The average particle size of the steel shot is in μm. s is the tensile strength of the steel plate, in MPa; K is the equipment constant, ranging from 0.10 to 0.18.
[0035] Preferred, When the temperature range is between 22 and 35, steel plates with Ra = 3.0 to 4.5 μm and a cleanliness level Sa of 3 can be stably obtained.
[0036] After EPS green cleaning surface treatment, an environmentally friendly corrosion inhibitor is used to form a protective film on the steel plate surface.
[0037] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0038] 1. Excellent comprehensive performance: Through the synergistic effect of Nb-Ti composite microalloying and ultra-fast cooling process, excellent comprehensive performance with tensile strength Rm≥700 MPa and elongation after fracture A≥18% is obtained under the condition of low carbon equivalent (Ceq≤0.45%), which meets the dual requirements of high strength and good plasticity for 700~750 MPa grade automotive beam steel.
[0039] 2. Ultra-fine microstructure: Ultra-fast cooling technology is used to cause the supercooled austenite to undergo phase transformation in the bainite transformation zone, resulting in a multiphase microstructure dominated by fine bainite laths, containing a small amount of ferrite and retained austenite, with an average grain size of 12 or finer, effectively achieving the synergy of fine grain strengthening and phase transformation strengthening.
[0040] 3. Significant precipitation strengthening: Within the bainitic phase transformation window (480~550 ℃), Ti and Nb simultaneously precipitate in the form of nano-sized (Ti,Nb)C particles, producing a strong precipitation strengthening effect with a strength contribution of 150~200 MPa, effectively compensating for the strength loss caused by the low carbon equivalent design.
[0041] 4. Green and environmentally friendly: The pickling process is completely eliminated. EPS green cleaning surface treatment is adopted, which uses water and steel grit as media to remove iron oxide scale. All media are recycled, and there is no acid mist or waste liquid discharge, realizing green and clean production.
[0042] 5. Excellent surface quality: The steel plate surface is smooth and clean after EPS treatment, with a surface roughness Ra=3.0~4.5 μm and a surface cleanliness Sa not lower than level 3, which meets the requirements of subsequent coating and stamping.
[0043] 6. Strong process adaptability: It can process steel plates with a thickness of 1.5~10 mm, covering thin to medium-thick specifications, thus expanding the product's application range. Detailed Implementation
[0045] The present invention will be further illustrated below with reference to embodiments. These embodiments are merely descriptions of the best mode of implementation and do not limit the scope of the invention in any way.
[0046] This invention is achieved through the following process steps: A medium-thin slab continuous casting process is adopted, with the slab thickness controlled at 135~200 mm; the slab is heated in a furnace to 1220~1260 ℃ and held for 1~3 h to ensure sufficient solid solution of alloying elements; a two-stage controlled rolling process is adopted, with the initial rolling temperature controlled at 980~1050 ℃ and the final rolling temperature at 800~850 ℃; immediately after final rolling, ultra-rapid cooling is implemented at a cooling rate ≥50 ℃ / s, rapidly cooling to the bainitic transformation zone at 480~550 ℃, followed by coiling, and the bainitic phase transformation is completed during the slow cooling process after coiling; the finished product thickness is 1.5~10 mm.
[0047] Before the EPS green cleaning surface treatment, the steel plate is straightened. The steel coil enters the EPS unit, and water and steel grit are used as the medium. The iron oxide scale on the surface of the steel plate is removed by high-speed rotating turbine. The turbine speed is set to 2000~2400rpm, and the steel plate travel speed is adjusted to 20~30 m / min. After treatment, an environmentally friendly corrosion inhibitor is used to form a protective film on the surface of the steel plate.
[0048] The following embodiments are merely some preferred implementations of the present invention and do not limit the scope and technical means of the invention in any way. The chemical composition of the embodiments of the present invention is shown in Table 1; the process parameters for continuous casting, heating, controlled rolling, ultra-fast cooling, and EPS of the steel in the embodiments of the present invention are shown in Table 2; and the mechanical property parameters and microstructure parameters of the steel in the embodiments of the present invention are shown in Table 3.
[0049] Table 1 Chemical composition (wt, %) of embodiments of the present invention 1 0.10 0.12 1.92 0.012 0.003 0.036 0.072 0.030 0.004 0.42 2 0.08 0.10 1.88 0.011 0.002 0.044 0.068 0.025 0.005 0.39 3 0.11 0.08 2.05 0.014 0.004 0.045 0.085 0.035 0.006 0.45 4 0.10 0.09 1.85 0.010 0.003 0.031 0.062 0.036 0.003 0.41 5 0.09 0.06 2.00 0.013 0.004 0.038 0.075 0.029 0.004 0.42 6 0.12 0.12 1.82 0.009 0.002 0.032 0.082 0.033 0.006 0.44 7 0.10 0.05 2.08 0.015 0.005 0.050 0.089 0.038 0.004 0.45 8 0.11 0.13 1.95 0.011 0.003 0.042 0.070 0.027 0.005 0.43 Table 2. Process parameters for continuous casting, heating, controlled rolling, ultra-fast cooling, and EPS processes in embodiments of the present invention. 1 135 1240 2.0 1000 830 60 520 2200 25 88.0 0.31 25.5 0.14 2 170 1230 1.5 1020 840 55 530 2100 26 80.8 0.30 24.2 0.13 3 170 1255 2.5 1030 820 65 500 2350 28 83.9 0.27 22.7 0.18 4 200 1220 1.8 980 810 50 540 2000 22 90.9 0.29 26.4 0.14 5 135 1245 2.0 1005 835 58 515 2250 24 93.8 0.28 26.3 0.13 6 170 1250 2.2 995 825 52 525 2150 23 93.5 0.28 26.2 0.15 7 200 1260 3.0 1015 845 68 490 2400 28 85.7 0.26 22.3 0.18 8 135 1235 2.0 990 820 55 535 2050 24 85.4 0.29 24.8 0.15 (Note: d The average particle size of steel shot is taken as 50-60 mesh, which corresponds to approximately 240 μm. s Take the measured tensile strength Rm, in MPa; in the table d / s During calculation d In μm, s (Measured in MPa.) Table 3 Mechanical properties and microstructure parameters of the steel in the embodiments of the present invention 1 4.0 635 765 19.5 3.5 3 85 15 12.5 2 2.5 610 740 22.5 3.1 3 82 18 13.0 3 8.0 680 815 18.5 4.1 3 88 12 12.0 4 6.0 620 755 22.0 3.6 3 83 17 12.5 5 3.0 645 780 20.5 3.3 3 86 14 13.0 6 5.0 660 795 19.0 3.8 3 87 13 12.0 7 10.0 695 828 18.0 4.0 3 90 10 12.0 8 5.0 630 770 20.0 3.7 3 84 16 12.5 As can be seen from Table 3, the tensile strength Rm of the steel in the embodiments of the present invention is 740~828 MPa, all of which reach the design strength of 700 MPa or more; the yield strength ReL is 610~695 MPa; the elongation after fracture A is ≥18%; the surface roughness Ra is 3.0~4.5 μm; and the surface cleanliness Sa is not lower than level 3.
[0050] It is hereby noted that the above embodiments are only for illustrating the technical concept and features of the present invention, and are not intended to limit the present invention. Any equivalent substitutions or modifications made without departing from the essence of the present invention fall within the protection scope of the present invention.
Claims
1. A Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate, characterized in that, By weight percentage, it comprises the following components: C: 0.08%~0.12%, Si≤0.15%, Mn: 1.80%~2.10%, Als: 0.030%~0.060%, Ti: 0.060%~0.090%, Nb: 0.020%~0.040%, N≤0.008%, P≤0.015%, S≤0.005%, with the balance being Fe and unavoidable impurities, and Ceq≤0.45%.
2. The Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate according to claim 1, characterized in that, The microstructure of the steel plate includes bainite, ferrite, and retained austenite, with a bainite volume fraction of 80% to 90%, a ferrite + retained austenite volume fraction of 10% to 20%, and an average grain size of grade 12 or finer.
3. The Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate according to claim 1, characterized in that, The steel plate has a yield strength ReL≥600 MPa, tensile strength Rm≥700 MPa, elongation after fracture A≥18%, surface roughness Ra=3.0~4.5 μm, surface cleanliness Sa not lower than level 3, and finished product thickness of 1.5~10 mm.
4. A method for manufacturing Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate according to any one of claims 1 to 3, comprising smelting, continuous casting of medium and thin slabs, heating, controlled rolling, ultra-fast cooling process, and EPS green and clean surface treatment process, characterized in that: Controlled rolling and ultra-fast cooling process: Two-stage controlled rolling is adopted, with a finishing rolling temperature of 980~1050 ℃ and a finishing rolling temperature of 800~850 ℃; after finishing rolling, an ultra-fast cooling process is adopted, which rapidly cools the temperature to 480~550 ℃ at a cooling rate of ≥50 ℃ / s before coiling. EPS green cleaning surface treatment process: After the steel coil is uncoiled and straightened, it enters the EPS unit. Using water and steel grit as the medium, a steel grit-water mixed slurry is sprayed through a high-speed rotating turbine to remove the iron oxide scale on the surface of the steel plate by physical impact.
5. The manufacturing method of an Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate according to claim 4, characterized in that, The process of continuous casting of medium and thin slabs is adopted, and the thickness of the continuously cast slab is 135~200 mm.
6. The manufacturing method of an Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate according to claim 4, characterized in that, The continuously cast billet is heated in a walking beam furnace at a temperature of 1220~1260 ℃ and held for 1~3 h.
7. The manufacturing method of an Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate according to claim 4, characterized in that, The steel grit has a mesh size of 50-60.
8. The manufacturing method of an Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate according to claim 4, characterized in that, In the EPS green cleaning surface treatment process, the turbine speed is 2000~2400 rpm and the steel plate travel speed is 20~30 m / min.
9. The manufacturing method of an Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate according to claim 4, characterized in that, The relationship between process parameters and steel plate properties is as follows: In the formula: n Turbine speed, rpm; v Let be the speed of the steel plate, in m·min -1 ; d The average particle size of the steel shot is in μm. σ is the tensile strength of the steel plate, in MPa; K is the equipment constant, ranging from 0.10 to 0.
18.
10. The manufacturing method of an Nb-Ti composite ultra-fast cooling 700 MPa grade green and clean surface automotive beam steel plate according to claim 9, characterized in that, The range is between 22 and 35.
Citation Information
Patent Citations
Production method of environment-friendly high-surface quality and pickling-free beamsteel
CN101906584A
Process for producing hot-rolled acid-pickled 610 L automobile frame steel strip with thin gauge and high elongation
CN103320683A
Hot rolled steel plate for 400MPa-level acid-pickling-free automobile structure and production method of hot rolled steel plate
CN105369134A
Surface quality control method of hot rolled steel coil
CN107649522A